Competence computation of attacks in wireless sensor network. Issue 7 (2nd October 2020) - Singh, Neha; Virmani, Deepali
Abstract: Wireless sensor network holds a very important space in daily routine. These sensors are connected to each other through Wireless Sensor Network and these networks collect data for various aspects. As this data is very important, it is prone to many attacks. Hence, we need to prevent the network from the attacks to maintain the integrity of data. In this paper, we have presented a framework to analyze various attacks in WSN. The framework is applied on black hole, flooding and gray hole attacks. The simulation of framework is done in ns2. A detailed analysis of packet delivery ratio, drop rate, throughput, density of packet drop, packet received, packet sent and success rate is done. We also conclude that our framework is best suited for analysis of attacks in WSN.